9-x+3x-2-9x=0

Simple and best practice solution for 9-x+3x-2-9x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-x+3x-2-9x=0 equation:


Simplifying
9 + -1x + 3x + -2 + -9x = 0

Reorder the terms:
9 + -2 + -1x + 3x + -9x = 0

Combine like terms: 9 + -2 = 7
7 + -1x + 3x + -9x = 0

Combine like terms: -1x + 3x = 2x
7 + 2x + -9x = 0

Combine like terms: 2x + -9x = -7x
7 + -7x = 0

Solving
7 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -7x = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -7x = 0 + -7
-7x = 0 + -7

Combine like terms: 0 + -7 = -7
-7x = -7

Divide each side by '-7'.
x = 1

Simplifying
x = 1

See similar equations:

| X/2-8=-14 | | 6log^8x+2=0 | | 6log^8+2=0 | | -22=g+15 | | 4/x=[72/40]2 | | h/5-h/3=7/15 | | 8(5-2v)-8=3v+13 | | -1/3x-1/2=3/5 | | -5+12=16x-2-15x | | 2(4x)=2x | | 4(3x+1)=3x-7x | | 7.7a-5.8a= | | 13y=12(y+8) | | X-(x*0.05)=800 | | 16y=40+8y | | -9(x-9)=7x+17 | | 1+44=-5(8x-9) | | -22=4(v-8)-6v | | 123-v=179 | | s^2=45-4s-s^2 | | .3/.2=18/? | | X/3- | | 6w+3w=27 | | 3x-450=2816 | | V/-3.3=-14.8 | | -5(5n-5)+3n=0 | | -3y-8x=12 | | 8sin(2pi/3) | | y=(x+2)(x-(3+i))(x+(3-i)) | | 6x+26=8x+36 | | =(x+2)(x-(3+i))(x+(3-i)) | | 9z+z=9z+5 |

Equations solver categories